Media Economic Evolution of Harian Kompas from Advertising Revenue to Digital Subscriptions - Ibnu Yunianto; Ragil Noviyanti; Athika Dwi Wiji Utami (Jurnal Nomosleca, 2025)
Internet and digital technologies have drastically transformed media consumption, reducing the time spent on newspapers and television. This research aims to analyze the adaptation of conventional media to digital disruption, focusing on Kompas.id's strategy in implementing a digital subscription business model. This study employs a descriptive qualitative approach. Data were collected through structured interviews and secondary data tracing. Informants were selected based on diverse professional backgrounds, making it a purposive sampling technique. The types of data used were primary data (interview results) and secondary data (documents, publications). Findings indicate that Kompas.idadopted a paywall as an "integration" strategy to maintain the value of its journalistic content. This implies a focus on the depth and quality of news, presenting serious content sought by readers amidst an information overload. This shift also triggeredsignificant internal changes within Kompas's newsroom, including adjustments to work culture and reorganization. This subscription model is expected to become a vital new revenue source, offsetting losses from print and advertising. Unique content qualityand trust factors are key attractions for subscribers.